The impact of alerting design on air traffic controllers' response to conflict detection and resolution - Kearney, Peter; Li, Wen-Chin; Lin, John J. H. (Elsevier, 2016)
Purposes: The research aim is to develop a better design of auditory alerts that can improve air traffic controllers’ situation awareness. Method: Participants are seventy-seven qualified Air Traffic Controllers. The experiment was conducted in the Air Traffic Control operational rooms of the Irish Aviation Authority at Shannon and Dublin. Participants were advised that the trials were in relation to the COOPANS Air Traffic Control. ANOVA with two between-subject factors (alerting designs and experience levels) were conducted to analyze the ATCO’s response time for three critical events. Bonferroni test was performed for post-hoc analysis on mean differences of response time. Results: There is a significant difference in ATCO’s response time between acoustic alert and semantic alert across STCA, APW and MSAW. No significant main effect of controllers’ experience on ATCO’s response time for STCA and APW. Also, there is no significant interaction between alerting design and experience level on ATCO’s response time across STCA, APW and MSAW. Conclusion: The results demonstrated that the acoustic alert deployed within the COOPANS ATM system provides level-1 Situational Awareness to ATCO’s compared with an semantic alert which provides not only level-1 of situational awareness for perceived alerts, but also level-2 and level-3 of situational awareness to assist ATCO understanding of critical events and therefore develop more suitable solutions. Consequently, human-centered design of a semantic alert can significantly speed up ATCO’s response to STCA, and APW. Furthermore, the sematic alert could alleviate expertise differences by promoting quicker response times for both novice and experienced air traffic controllers.
Keywords: Air Traffic Management; Alerting Design; Human-Centered Design; Semantic Alert; Situation Awareness